Risk factors for apical periodontitis – review of literature - Sopińska, Katarzyna; Bołtacz-Rzepkowska, Elżbieta (Journal of Stomatology, 2015)
Introduction. The incidence of apical periodontitis varies from 30% to 52% in different populations. The availability of diagnostic radiology allows detection of apical pathology, which, in many cases, develops without any clinical symptoms. Next to early diagnosis and effective treatment, it is extremely important to identify factors that affect the occurrence of this condition. Aim of the study. To present risk factors for apical periodontitis based on reports in literature. Material and methods. The introduced material is the result of the review of articles conducted in Medline/ Pubmed using the following phrases: “risk factor for apical periodontitis”, “risk indicators for apical periodontitis”, “prevalence of apical periodontitis”, “prevalence of apical lesions”. Results. There are tooth-specific and non-tooth-specific risk factors for developing pathologies in the periapical region. The former include: tooth decay, coronal restoration, root canal treatment, the presence of intra-radicular posts and dental crowns. Among non-tooth-specific factors that predispose to apical periodontitis are: socio-economic situation of the patient, patient’s attitude to dental treatment, smoking and systemic disease. Conclusions. Identification of risk factors for apical periodontitis enables the selection of patients who have the highest probability of the occurrence of apical lesions. According to literature, the main tooth-specific risk factor is the unsatisfactory quality of the root canal treatment. Clinicians can reduce the negative factors during the therapeutic process, but they cannot impact patient-related factors, such as systemic diseases or addictions, whose elimination is often difficult or impossible. However, all risk factors should be considered as a predictor during treatment planning.